MENINGKATKAN PEMAHAMAN KONSEP GEOMETRI MENGGUNAKAN BENDA MANIPULATIF PADA SISWA KELAS V SD MUHAMMADIYAH 4 BATU - Anik Novianti (INSPIRAMATIKA, 2015)
The aims of this research were to improve the fifth grade of Muhammadiyah 4 Batu Elementary School students’ understanding of geometry concept by using manipulative objects. This research was a Classroom Action Research with qualitative approach. The research was conducted to 32 fifth grade students of elementary school and the subject of the interview consisted of 4 students which were chosen based on the results of the final test. Learning activities of the research were held in two cycles. The first cycle learning activities were not successful since the final test had not yet fulfilled the minimum mastery criteria. In the second cycle, the successful criteria had been fulfilled, in which the class got 84% for the minimum mastery criteria, which passed the classical KKM 80%. The results of the study were as follows: 1) learning by using manipulative objects can improve the understanding of geometry concept especially for properties of plane, 2) students looked happy during the teaching and learning process by using manipulative objects.